Skrining Fitokimia Tumbuhan Potensi Obat Kanker Kolorektal Begonia Medicinalis Ardi & D.C. Thomas - Ardiputra, Muh. Akbar; Musjaya M. Guli; Andi Saifah; Santi; Bambang Sardi; Wafiq Nurfadilah; Mohammad Rivaldi Putra Pratama; Afifah Islamia (Jurnal Kedokteran Universitas Palangka Raya, 2024)
Cancer is a condition in which cells or tissues undergo abnormal progressive growth. Colorectal cancer is cancer that occurs in the colon to rectum organs of humans. Alternative therapy for colorectal cancer treatment is the use of herbs such as Begonia medicinalis Ardi & D.C. Thomas. This study aimed to screen the bioactive compounds in the Begonia medicinalis Ardi & D.C. Thomas. extract and its potential as a colorectal cancer drug. This research consists of two stages, namely the extraction stage using the maceration method and the screening stage. The results showed that the extract of Begonia medicinalis Ardi & D.C. Thomas. positively contains flavonoids, alkaloids, and saponins. These bioactive compounds have potential activity as preventive and curative agents for colorectal cancer through several mechanisms, including suppressing oxidative stress, inhibiting CDK activity, suppressing intestinal inflammation, and increasing floranormal diversity and probiotic barrier activity in the intestine.